Highly regio- and stereoselective synthesis of bis-sulfanyl substituted conjugated dienes by copper–palladium cooperative catalysis. Issue 3 (16th December 2020) - Li, Yuan; Wu, Jin; Li, Hui; Sun, Qian; Xiong, Lixue; Yin, Guodong
Abstract : An efficient one-pot method for the synthesis of ( Z, Z )-isomers of 1, 4-bis(sulfanyl)-1, 4-diaryl-1, 3-butadienes by the cooperative catalysis of Cu(Xantphos)I/Pd(OAc)2 and a base has been developed. Abstract : An efficient one-pot method for the synthesis of symmetric ( Z, Z )-isomers of 1, 4-bis(sulfanyl)-1, 4-diaryl-1, 3-butadienes from the easily available aryl halides, 1, 4-bis(trimethylsilyl)butadiyne and thiols by the cooperative catalysis of Cu(Xantphos)I and Pd(OAc)2 and a base has been developed. Preliminary mechanistic studies revealed that the reaction probably follows the double-Sonogashira coupling/double hydrothiolation pathway, in which two C–C bonds and two C–S bonds were formed sequentially. This protocol features a good substrate scope with a broad range of functional group tolerances, simplicity of operation, and high regio- and stereoselectivity.